A hydroquinone-specific screening system for directed P450 evolution - Weingartner, Alexandra M. (Appl Microbiol Biotechnol, 2018)
The direct hydroxylation of benzene to hydroquinone (HQ) under mild reaction conditions is a challenging task for chemical catalysts. Cytochrome P450 (CYP) monooxygenases are known to catalyze the oxidation of a variety of aromatic compounds with atmospheric dioxygen. Protein engineering campaigns led to the identification of novel P450 variants, which yielded improvements in respect to activity, specificity, and stability. An effective screening strategy is crucial for the identification of improved enzymes with desired characteristics in large mutant libraries. Here, we report a first screening system designed for screening of P450 variants capable to produce hydroquinones. The hydroquinone quantification assay is based on the interaction of 4-nitrophenylacetonitrile (NpCN) with hydroquinones under alkaline conditions. In the 96-well plate format, a low detection limit (5 μM) and a broad linear detection range (5 to 250 μM) were obtained. The NpCN assay can be used for the quantification of dihydroxylated aromatic compounds such as hydroquinones, catechols, and benzoquinones. We chose the hydroxylation of pseudocumene by P450 BM3 as a target reaction and screened for improved trimethylhydroquinone (TMHQ) formation. The new P450 BM3 variant AW2 (R47Q, Y51F, I401M, A330P) was identified by screening a saturation mutagenesis library of amino acid position A330 with the NpCN assay. In summary, a 70-fold improved TMHQ formation was achieved with P450 BM3 AW2 when compared to the wild type (WT) and a 1.8-fold improved TMHQ formation compared to the recently reported P450 BM3 M3 (R47S, Y51W, A330F, I401M). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00253-018-9328-3) contains supplementary material, which is available to authorized users.